EFFECT OF NITROGEN APPLICATION THROUGH DIFFERENT COMBINATIONS OF UREA AND FARM YARD MANURE ON THE PERFORMANCE OF SPRING MAIZE (Zea mays L.) - A. U. Mohsin; J. Ahmad; A. U. H. Ahmad; R. M. Ikram; K. Mubeen (Journal of Animal and Plant Sciences, 2012)
Integrated use of mineral fertilizers and organic material is considered as a good and healthy approach for sustainable crop production. This hypothesis was tested on maize crop through field experiment, laid out in randomized complete block design with three replications, having six treatments with a net plot size 3.0 m x 6.0 m. The treatments were; control, 100% N through FYM, 25% N through urea and 75% N through FYM, 50% N through urea and 50% N through FYM, 75% N through urea and 25% N through FYM and 100% N through urea. The crop was sown on the ridges having rows 75 cm apart with plant to plant distance of 15 cm distance. The data on yield and crop growth parameters were recorded by using standard procedures and was statistically analyzed using Fisher’s analysis of variance technique and least significant difference (LSD) test (P < 0.05) was employed to compare the treatment means. Application of 50% N from Urea + 50% from FYM produced longer cobs (18.57 cm), maximum cob weight (216.4 g), maximum 1000-grain weight (279.1 g), higher grain yield (5793 kg ha-1) and maximum biological yield (14880 kg ha-1). On the basis of these results, it can be concluded that 50% N through urea and 50% N through FYM should be used for spring maize in order to get maximum yield.
Keywords: Maize; Farmyard manure; Urea; Growth; Yield.